User-interface design and evaluation in a mobile application for detecting latent tuberculosis - Farao, Jaydon Ethan (Division of Biomedical Engineering, 2020)
Treatment and monitoring of tuberculosis have been met with various interventions to reduce its prevalence. One such intervention, to detect and prevent latent tuberculosis infection (LTBI), is the tuberculin skin test (TST), for which an induration response on a patient’s arm is an indication of LTBI. The test requires the patient to return to a clinic 48 to 72 hours after TST administration for assessment of the response. This is a challenge because of financial and accessibility obstacles, especially in under-resourced regions. A mobile health (mHealth) application (app) has been developed for remote assessment of the response to the TST. The previous version of the LTBI screening app, however, had usability limitations. The app is intended for use by patients and healthcare workers; thus, ease of use is important. There is a lack of literature on the usability of mHealth apps, especially in under-resourced settings. In this project, the user interface of the app was redesigned and tested. The Information Systems Research (ISR) framework was integrated with design thinking for this purpose. The project included creating mock-ups of the interface which were iteratively prototyped with ten student participants, adjusted, and assessed according to the user feedback. Thereafter, the Android Studio software was used to adjust the user interface based on the insights gained through the progression of prototypes. The usability of the updated app was tested and assessed with ten healthcare workers at a community health clinic in Khayelitsha in Cape Town, South Africa. Data collection and analysis comprised both qualitative and quantitative methods. Observations, the “think aloud” approach, and the post-study system usability questionnaire were used for data collection. Student participants highlighted various usability limitations of the app during each iteration. The major usability limitations included: the complex image capture protocol, misunderstanding of instructions, and time taken to capture images. Engagement with students allowed for improvement of the app interface and enabled adequate preparation for testing in the field with end-users. Furthermore, improving the app interface before engaging with healthcare workers, enabled context specific limitations that would affect the usability of the app, to be explored during the field testing. These included safety concerns when using the app and the privacy of health information. Future work should explore how these concerns, as well as other social factors, affect usability. Furthermore, improving the image capture protocol is required for improving the usability of the app.